2006
DOI: 10.1159/000089024
|View full text |Cite
|
Sign up to set email alerts
|

Terbinafine-Induced Subacute Cutaneous Lupus Erythematosus

Abstract: Background: Nearly 10% of lupus erythematosus (LE) are drug induced. More than 60 different drugs are involved in iatrogenic LE. We report herein 3 cases of terbinafine-induced LE. Observations: Three patients receiving terbinafine for a suspected dermatophytic infection developed a subacute cutaneous LE, within 7 weeks following terbinafine introduction. The patients’ medical history included sicca syndrome, lung carcinoma and Kikuchi disease, respectively. Clinical remission occurred within 15 weeks followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 56 publications
0
18
0
2
Order By: Relevance
“…To the authors’ knowledge, this type of reaction has never been reported before in cats. However, multiple and often serious, skin reactions such as erythema multiforme, erythroderma, urticaria, and subacute cutaneous lupus erythematosus have been reported in humans treated with terbinafine 21,22 . Importantly, these cats developed the cutaneous reaction after discontinuing the terbinafine.…”
Section: Discussionmentioning
confidence: 99%
“…To the authors’ knowledge, this type of reaction has never been reported before in cats. However, multiple and often serious, skin reactions such as erythema multiforme, erythroderma, urticaria, and subacute cutaneous lupus erythematosus have been reported in humans treated with terbinafine 21,22 . Importantly, these cats developed the cutaneous reaction after discontinuing the terbinafine.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-SSA/Ro-associated drug-induced LE is believed to be an entity distinct from classical drug-induced LE, because the former is characterized primarily by cutaneous disease and lacks antihistone antibodies [5]. The causal drugs for this disease are variable, such as hydrochlorothiazide, calcium channel blockers, angiotensin-converting enzyme inhibitors, griseofulvin and terbinafine [5,7,8,9]. It is well known that FU agents induce DLE-like eruptions in Japan [1].…”
Section: Discussionmentioning
confidence: 99%
“…In all three, along with positive ANA, patients also had antibodies to Ro/SS-A and/or La/SS-B, as is characteristic in SCLE. Including the patient described here, there are currently (as of April 2008) 28 reports in the English, French, and German literature of terbinafine-induced LE ( Table 1; [4][5][6][7][8][9][10][11][12][13][14][15]). In one patient, there was concomitant onset of Stevens-Johnson syndrome [13]; in all patients, the skin lesions and/or documented antibody status are compatible with the presence of SCLE.…”
Section: Discussionmentioning
confidence: 99%